The Role of Literary Works as Alternative Historical Narrative: Antara Dendam dengan Perjuangan by Ali Jusoh - Chow, Sheat Fun; Abdullah, Mohd Syukor (Malay Literature, 2022)
Historical literary works inject soul and life into historical events contained in the texts. Local historical literary works provide an alternative history that deepens the reader’s understanding of the struggles of past Malay warriors. Antara Dendam dengan Perjuangan by Ali Jusoh serves as an alternative history that is vivid and provides a contemporary meaning that elevates the novel as a document filled with the struggles of the Malays in their fight against the colonizers. This article aims to analyse the psychological aspect of the main characters of this text. In doing so, historical events are reinterpreted. In the novel, the uprising of Pahang warriors is not only narrated, but through the New Historicism approach, readers can better understand the events in history. The novel narrates not only past events, but also includes the tones and nuances of silenced voices of the past. This article applies the New Historicism approach, particularly that of Greenblatt (1989), which affirms the connection between a text and its context of setting and time. This article also applies the idea advocated by Hashim (2003) that New Historicism contributes to the deconstruction of history, especially that of postcolonial societies. It also focuses on selected events that expose the characters’ psyche in the novel, thus demonstrating that history and literature complement each other. Through New Historicism and the study of selected characters in the novel, particular events are re-lived and given new meaning and contemporary interpretation. Full text :  PDF